Role of Modern Accounting in Economic Development of Emerging Economies - Lasya K R, R. Satheeshkumar, Gururaj F Duragannavar, Shwetha L S (Journal of Informatics Education and Research, 2023)
This research aims at identifying the role of modern accounting in building up strong economy in emerging economics, in this approach descriptive analytical approach was used to clarify the theoretical framework through some previous studies and hypothesis testing. The study tool was the questionnaire. The present study proved that the modern accounting contributes significantly to the economic development in the emerging economics based on accounting standards. They have been following the GAAP format to bring the globe into one system. The study recommended the importance of enhancing the role of accounting in economic development and addressing the difficulties and challenges in adoption of IFRS investigate the role that country-level institutional quality plays in the relationship.